Car Modification Workshop Design With A High-Tech Architectural Approach In Medan City (International Journal of Architecture and Urbanism, 2023)
The design of a car modification workshop in Medan is intended for car modification enthusiasts so they can develop their hobbies and are designed using a High-Tech Architectural design. Car users in the city of Medan have reached 42,397, so this figure can affect the number of car modification enthusiasts. In the city of Medan itself, there are not too many car modification workshops that provide multi-functional services with supporting facilities, so it is difficult to find a variety of modification options. The design of a car modification workshop in the city of Medan with high-tech architecture aims tobe able to meet the demand for vehicle sales services, engine servicing, modifications, and other facilities on a large scale due to the high market interest. This car modification workshop is specifically designed and has been limited according to the concept of the user, actor, type of activity, space requirements and building analysis. By using the basic High-Tech theme, the concept of structural configuration style is applied in such a way. It turns out that High-Tech Architecture is very much influenced by current scientific advances and innovations so that it has many functions that are useful for many people. This design is expected to be able to overcome the problems of the people in Medan to have the latest innovations and accommodation for technological advances because it has a futuristic impression along with the times and provides its own style to attract the attention of visitors.